(untitled) (Annals of Medical Research, 2023)
Aim: To evaluate the presence of kinesiophobia and its potential effects on pain, depression, disease activity and quality of life in patients with ankylosing spondylitis (AS). Materials and Methods: The study included 58 AS patients and 55 healthy controls. Tampa Kinesiophobia Scale (TKS) was used to evaluate the presence of kinesiophobia, Visual Analogue Scale (VAS) for severity of pain, Beck Depression Index (BDI) for depression level, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) for disease activity, Bath Ankylosing Spondylitis Functional Index (BAS-FI) for functional status, and Ankylosing Spondylitis Functional Index (ASQoL) for Quality of life. Results: In patient group, kinesiophobia rate was statistically significantly higher (68%) compared tothe healthy control subjects (27%) (p<0.001). TKS score, VAS pain level, and BDI levels were significantly higher in patients with AS compared to the healthy controls (for all p <0.001). In the AS group, patients with high kinesiophobia score had higher VAS, BDI, BAS-FI, BASDAI, and ASQoL scores compared to the patients with low kinesiophobia score (p<0.001) and the relationships between kinesiophobia and VAS, BDI, BAS-FI, BASDAI, and ASQoL scores (for all p<0.001) were significant.In addition, there was no significant relationship was found between kinesiophobia and age, and disease duration (p>0.05). Conclusion: Kinesiophobia is more common in patients who had AS than in healthy control subjects, and presence of kinesophobia is related toimpaired quality of life and increased pain. Therefore, we propose that strategies to increase awareness of movement fear, cognitive behavioral therapy and physical activity should be involved in the treatment programs.